2005
DOI: 10.1590/s0103-50532005000800016
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative HPLC analysis of sesquiterpene lactones and determination of chemotypes in Eremanthus seidelii MacLeish & Schumacher (Asteraceae)

Abstract: Eremanthus seidelii MacLeish & Schumacher tem ocorrência restrita ao cerrado, em torno do reservatório de Furnas (MG), em habitats que vêm sendo seriamente deteriorados pela ação humana. A presente investigação fitoquímica mostrou, como metabólitos secundários majoritários das folhas de E. seidelii, as lactonas sesquiterpênicas (LS) 4β,5-diidro-2',3'-diidroxi-15-desoxigoiazensolídeo (1) e 4β,5-diidro-1',2'-epoxi-eremantolídeo-C (2); uma metodologia foi desenvolvida em CLAE para sua análise quantitativa. A anál… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
0
14
0
5
Order By: Relevance
“…To date, STLs from the furanoheliangolide type have been considered as characteristic metabolite and chemotaxonomic marker of subtribe Lychnophorineae due to its isolation from plants of some genus of this subtribe. [28][29][30] However, as can be observed in these results, STLs cannot be considered as chemotaxonomic markers, at least for the species L. ericoides, due to being detected in only one population. Nevertheless, they could be considered as characteristic of a chemotype into the species L. ericoides.…”
Section: Resultsmentioning
confidence: 93%
“…To date, STLs from the furanoheliangolide type have been considered as characteristic metabolite and chemotaxonomic marker of subtribe Lychnophorineae due to its isolation from plants of some genus of this subtribe. [28][29][30] However, as can be observed in these results, STLs cannot be considered as chemotaxonomic markers, at least for the species L. ericoides, due to being detected in only one population. Nevertheless, they could be considered as characteristic of a chemotype into the species L. ericoides.…”
Section: Resultsmentioning
confidence: 93%
“…Por outro lado, estudo recente mostrou que os metabólitos secundários de uma espécie vegetal selvagem, amostrada diretamente em seu habitat em três diferentes populações, se mantiveram em concentrações constantes durante os dois anos do estudo, demonstrando, portanto, que em alguns casos o metabolismo secundário pode não se alterar em função de fatores climáticos, temporais ou ambientais 167 .…”
Section: Conclusõesunclassified
“…Regarding literature data, it can be observed that sequential partition of ethanolic extract from Eremanthus species with solvents of increasing polarity allow the achievement of a sesquiterpene enriched dichloromethane fraction (Sakamoto et al, 2005(Sakamoto et al, , 2010. Thus, chromatographic fingerprint analysis of the dichloromethane fraction (ECD) from leaves of Eremanthus crotonoides (DC.)…”
Section: Resultsmentioning
confidence: 99%
“…Studies carried out for species from this genus indicated the predominance of sesquiterpene lactones from the furanoheliangolide class (goyazensolide and eremantholide types) as their characteristic constituents (Vichnewski & Gilbert, 1972;Raffauf et al, 1975;Bohlmann et al, 1980Bohlmann et al, , 1981Bohlmann et al, , 1982Vichnewski et al, 1989;Rüngeler et al, 1998;Sacilotto et al, 2002;Sakamoto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%